Characterization of the complete mitochondrial genomes of two sea cucumbers, Deima validum and Oneirophanta mutabilis (Holothuroidea, Synallactida, Deimatidae): Insight into deep-sea adaptive evolution of Deimatidae - Wendan Mu; Jun Liu; Haibin Zhang (PLoS ONE, 2025)
The deep-sea is the largest and most extensive ecosystem on our planet with limited food availability, extreme pressure reaching hundreds of bars, perpetual darkness, frigid temperatures, and minimal oxygen levels. Mitochondria plays a key role in energy metabolism and oxygen usage, thus it may undergo adaptive evolution in response to pressures from extreme harsh environments. In this study, we present the mitochondrial genome sequences of the sea cucumbers Deima validum and Oneirophanta mutabilis collected from the South China Sea. To our knowledge, they are the first reported mitogenomes from the family Deimatidae. Similar to other sea cucumbers, both mitogenomes contain 13 PCGs, 2 rRNA genes, 22 tRNA genes (including duplication of trnS and trnL) and 1 non-coding regions. The genes in both species are distributed on the positive and negative strands, with six genes encoded on the L-strand and 31 genes encoded on the H-strand. We compared the order of genes from the 13 available holothurian mitogenomes and found a novel gene arrangement in D. validum. Phylogenetic analysis revealed that D. validum clustered with O. mutabilis, forming the deep-sea Deimatidae clade. The analysis of individual genes revealed the presence of three sites (90 L, 147 S, 192 V) in nad2 and one site (28 S) in nad5 with high posterior probabilities indicating positive selection. By comparing these features with those of shallow sea cucumbers, we predict that nad2 and nad5 may provide valuable insights into the molecular mechanisms at the mitochondrial level involved in Deimatidae's adaptation to the deep-sea habitat.